Survival of probiotic microflora in Argentinian yoghurts during refrigerated storage - Vinderola, Celso Gabriel (2000)
The survival of Bifidobacterium bifidum BBI and Lactobacillus acidophilus LAI in reduced-fat (liquid) and full-fat (set) yoghurts produced with two commercial lactic starter cultures (SID and SISD) was investigated. The viability of the probiotic bacteria was also assayed in milk acidified with lactic acid at different pH values. Samples were stored at 5°C for up to 4 weeks. There was a great variability in the survival ability of the probiotic cultures in the two yoghurt types L. acidophilus LAI demonstrated, in general, a lower resistance to the yoghurt environment than B. bifidum BBI. On the other hand, the full-fat yoghurt was a more inhibitory medium than the reduced-fat one, especially for B. bifidum BBI. Regarding the lactic starters used, the results showed that the culture SISD was clearly more inhibitory for both probiotic organisms than the culture SID. The loss of cell viability in yoghurt samples was different (higher in some cases and lower in others) from that due to lactic acid only. In general, pH values of 4.5 or lower jeopardised the cell viability of the probiotic organisms in yoghurt stored at 5°C. This work shows the importance of selecting a suitable combination of probiotic strains and starter cultures when different yoghurt types are formulated.